Skip-beat! 07 - Nakamura, Yoshiki (Shojo beat manga., 2007)
All Kyoko's dreams are coming true! She's got a best friend (okay, so Moko still needs to come to terms with their bosom-buddyhood, but she's learning). She's finally going to high school (so what if a mean girl is picking on her --Kyoko knows how to deal with bullies). And she's landed a spot in Sho's new video (Yes! Revenge! Bwa ha ha ha!). Life doesn't get any better than this.